The Effect Of Service Quality And Company Image On Customer Satisfaction At Indonesian Reasuransi Company - Karunia, Muhammad Nur (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2021)
In addition to profits, the thing that needs to be considered and maintained by the company is customer satisfaction. In other words, maintaining customer satisfaction, is tantamount to maintaining profits and the survival of the company. This study was conducted to analyze the reinforcing factors of customer satisfaction in Indonesian reinsurance companies. The research method uses quantitative with sub-derived survey methods. This study uses regression-based statistical analysis, with a total sample of 118 people. The results of the study stated that service quality and company image are two different things, but have an influence on customer satisfaction. Service quality is a direct factor, which occurs when customers interact with the company. While the company's image is an indirect factor that is psychological, which affects customer perceptions and ratings, the more popular the company's name is, the better it is perceived, and gives its own satisfaction as a customer.